Trying to Stay Ahead of the Curve in Chile S Economic Development: Exploring a Way Out of the Middle-Income Trap Through Pragmatic Export Development - Dingemans-Calderon, A (Blackwell Publishing Ltd, 2016)
Underneath impressive growth levels, the Chilean economy displays signs of being caught in a middle-income trap. It has been unable to improve its productivity, increase the added value of its exports or upgrade its value chain. Its economy cannot compete either with low-wage countries or highly productive, innovative countries. Its export strategy based on export promotion seems to have outlived its usefulness. It achieved remarkable quantitative success, but must now attend qualitative attributes. Instead of regarding market-driven export promotion and state-led export development as substitutes, this article proposes to view them as alternatives in different stages of development. To choose the appropriate time, more attention should be given to non-traditional, structural indicators, like export sophistication and political-institutional capabilities. © The Authors 2016. Development Policy Review © 2016 Overseas Development Institute